(untitled) (Педагогіка вищої та середньої школи, 2004)
In Matukovoj Anna I. article "Personal-guided training as the way of stimulation of physical activity of students of higher educational institutions" is shined a problem of increase of impellent activity at the future experts. The researcher pays attention to features of construction educational process with youth and proves necessity of introducing new programs and forms of employment of physical training.